Density functional theory study of the electronic and optical properties of pure and magnesium doped Β-tricalcium phosphate compound - Bakheet, A. M. A. (Penerbit UTM Press, 2016)
β-Tri-calcium phosphate material (β-TCP), have attract a wide interest in the material science and medical science applications, due to its excellent biocompatibility and its identical chemical compositions to the natural teeth and bones. For that reason, (β-TCP) compound is widely used as biocompatible ceramics in medical and dental science applications. However, research shows that, pure β-TCP material has lower ability to stimulate the growth of natural bone and teeth as needed. Therefore, in order to address this deficiency magnesium impurity is used to replace calcium in the matrix of pure β-TCP to enhance its electronic and optical properties which are not present in the pure one. Thereby, its biological performance becomes improved. By changing the chemical composition of β-TCP to be similar to the mineral compositions of the natural teeth and bones. This will give more insight in fabrication of biomaterial devices for replacing, repairing and rebuilding the broken or damaged human teeth and bones. Here, we present the study of compound β-TCP using density functional theory (DFT). For the calculations, we used full potential linear augmented plane wave method (FPL-APW), along with generalized gradient approximations (GGA) potential. The band gap values of 5.2 eV and 3.4 eV are obtained for the pure and Mg-doped β-TCP, respectively. These results are in good agreement with the experimental values. Our results show peaks which correspond to the refractive index, complex dielectric function, optical conductivity, optical reflectivity, extinction coefficient, absorption efficient, and electron energy loss. These peaks are shifted towards the higher energy values for the pure and Mg-doped β-TCP material. The obtained results have more significance for increasing the quality of electronic and optical properties of this material and offer more evidences to synthesize enhanced β-TCP material for dental and medical applications.